Optimization of the brake factor for an S-cam foundation brake using RSM - Sayim, Irfan (Strojniški vestnik, 2016)
The brake factor (BF) scales the vehicle%s braking force; therefore, the vehicle brake performance variation due to the foundation brake can be attributed to the BF variation. In this work, the BF reduction is considered in the design stage of an S-Cam foundation brake within dimensional properties in order to have stable, predictable and improved vehicle brake performance. First, brake lining wear types were defined and then actuation cam-roller position effects were formulated. Dimensional parameters were varied within certain design-possible ranges to quantify BF variation theoretically. The response surface method (RSM) was used to identify the BF-reduced combination of dimensions within theoretical results. In the meantime, a new testing procedure was introduced and then a new testbed was designed and built to validate relative improvement of BF experimentally without thermal effects on friction. It was investigated that a substantial improvement (22.93 %) on BF could be obtained if appropriate dimensions were selected in the design stage.
Keywords: bobnasta zavora na osi z S-odmikalom; kolutna zavora; metoda odzivne površine; obraba oblog; položaj odmikalnega valja; zavorni faktor